ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT MENJADI GIG WORKER - Darmawan, Ryandio Kris; Aminnullah Achmad Muttaqin (Journal of Development Economic and Social Studies, 2023)
The development of the gig economy sector in recent years has opened up new possibilities for flexible types of jobs, both in terms of time and location. This potential is also present in Malang City, and there is a need for a better understanding of the factors that may influence people's decisions to become gig workers. The objective of this research is to examine the influence of several factors such as technological skills and internet access, job opportunities, time flexibility, income security, financial benefits, and lifestyle on people's decisions to become gig workers. This study found that the variables examined have a positive relationship with people's decisions to become gig workers in Malang City.